A fisionomia da paisagem no Curso Fluvial Inferior - CFI da bacia hidrográfica do rio Andirá, município de Barreirinha-AM - Carneiro, Zaqueu de Souza (Brasil, 2025)
The objective of this thesis was to analyze the physiographic aspects that shape the current landscape of the Lower River Course (LRC) of the Andirá River, in the municipality of Barreirinha-AM. To achieve this, it was necessary to address the theoretical contributions of analysis categories that link the landscape and the physiognomy of the physiographic elements of the LRC of the Andirá River, as well as to characterize the physical-environmental attributes that form the physiographic landscape of the study area. The methodological strategy adopted in the research was based on a systemic approach, using a qualitative-quantitative approach. The study was conducted in an interrelated manner with data from bibliographic research; fieldwork for the analysis categories; data validation and photographic recording; office work with Geographic Information Systems (GIS) for the production of cartographic material using QGIS, PlanetScop images, and SRTM – INPE data, along with IBGE and CPRM data. The results show that understanding the evolution of the concept of Landscape is essential for its relationship with the elements of geodiversity. Furthermore, the Geosystemic approach helps in understanding the fluvial systems of Western Amazonia, classified as black, white, and clear water rivers. The physiognomy of the landscape in the LRC of the Andirá River is characterized by the predominant environmental attributes of the Geomorphological Units of Floodplain (Holocene alluvium, Amazonian plain, fluviomorph soils, floodplain vegetation, and low altitudes) and Upland (Alter do Chão Formation, Yellow Latosols, Dense Ombrophilous Forest and secondary vegetation). The Andirá River's river cliffs are active, low, and not very extensive formations, commonly referred to as "barriers." The influence of the hydraulic damming by the Paraná do Ramos resulted in a flooded mouth extending 31.7 km, with an average width of 5 km, completely reshaping the landscape physiognomy along both the right and left banks. The Andirá River is classified as an olive-green river, with the color tending to darken during the flood period. The fluvial physiography of the seven analyzed sub basins (Sbhs) shows an average area of 77 km², with an average width ranging from 2.16 to 10.53 km, and they exhibit a median tendency to flooding based on basin shape parameters. The limnological characteristics of the SBH reveal an average drainage density of 1.67 km², a fluvial hierarchy of the 3rd to 5th order, a dendritic drainage pattern, and endorheic flow. The study of landscape physiognomy in hydrographic systems is relevant for surveying current environmental conditions and also supports the development of appropriate strategies for the occupation and use of water resources in the Lower River Course of the Andirá River in Barreirinha-AM.